Evaluation of attitude and behavioural intention towards auditing services among small and medium enterprises in Ghana - VALERIUS ENAM DZIMALE (knust, 2024)
A thesis submitted to the institute of distance learning, Kwame Nkrumah university of science and technology in partial fulfillment of the requirements for the degree of Master of science in accounting and finance